OPERATING MEMBER OF TAPE RECORDER (1980)
PURPOSE:To optimize the unit to remote operation, by constituting the unit with the operation buttons located in correspondence with individual operation lever and the holder holding the operation buttons movably. CONSTITUTION:After mounting the operating buttons 31-36, limit plate 92, and key holder 60 fitting the spring 74 to the bosses 71, 72 of the cabinet, the latch pieces 51-56 of the operating buttons 31-36 are inserted to the notches 21-26 respectively for the operation levers 11-16, and the mechanism and the holder are fixed to the cabinet 70. In this state, since the notches 21-26 and the latch pieces 51-56 are latched not tightly, no external influence is not affected and the operating buttons 31-36 are subjected only to the effect of the force of the spring 74. Accordingly, the play of the operating levers 11-16 and the unarranged decoration buttons 41-46 can be absorbed between the notches and the latch pieces. Thus, this is used in optimum usage in remote location between main body of the mechanism and the operating section.